2020
DOI: 10.1111/1471-0528.16381
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal anxiety and obstetric decisions among pregnant women in Wuhan and Chongqing during the COVID‐19 outbreak: a cross‐sectional study

Abstract: Objectives To investigate the mental status of pregnant women and to determine their obstetric decisions during the COVID‐19 outbreak. Design Cross‐sectional study. Setting Two cities in China––Wuhan (epicentre) and Chongqing (a less affected city). Population A total of 1947 pregnant women. Methods We collected demographic, pregnancy and epidemic information from our pregnant subjects, along with their attitudes towards COVID‐19 (using a self‐constructed five‐point scale). The Self‐Rating Anxiety Scale (SAS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
190
8
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(227 citation statements)
references
References 36 publications
15
190
8
14
Order By: Relevance
“…Most of the studies published in the last months on the effect of the Covid-19 pandemic on pregnancy and childbirth have mainly focused on medical conditions and risk factors and have attempted to pinpoint the measures and clinical recommendations required to contain the Covid-19 spread (e.g., Chen et al, 2020;Liang and Acharya, 2020). The scant literature that has addressed the psychological impact of the Covid-19 pandemic on expectant and postpartum women has found higher levels of anxiety and depressive symptoms among participants when compared to similar cohorts assessed before the outbreak (Ceulemans et al, 2020;Lebel et al, 2020;Liu et al, 2020;Patabendige et al, 2020). An Italian study investigating the psychological effects of the pandemic on pregnant women found a significant change in their expectations toward pregnancy and childbirth as well as an increase in their concerns and distress, especially if they had a previous history of psychological distress in press (Ravaldi et al, 2020).…”
Section: Psychological Well-being During the Covid-19 Pandemicmentioning
confidence: 99%
“…Most of the studies published in the last months on the effect of the Covid-19 pandemic on pregnancy and childbirth have mainly focused on medical conditions and risk factors and have attempted to pinpoint the measures and clinical recommendations required to contain the Covid-19 spread (e.g., Chen et al, 2020;Liang and Acharya, 2020). The scant literature that has addressed the psychological impact of the Covid-19 pandemic on expectant and postpartum women has found higher levels of anxiety and depressive symptoms among participants when compared to similar cohorts assessed before the outbreak (Ceulemans et al, 2020;Lebel et al, 2020;Liu et al, 2020;Patabendige et al, 2020). An Italian study investigating the psychological effects of the pandemic on pregnant women found a significant change in their expectations toward pregnancy and childbirth as well as an increase in their concerns and distress, especially if they had a previous history of psychological distress in press (Ravaldi et al, 2020).…”
Section: Psychological Well-being During the Covid-19 Pandemicmentioning
confidence: 99%
“…Earlier studies reported that pregnant women from different countries experienced different levels of anxiety or depression during the early or peak period of COVID-19 [5][6][7][8]12]. In Wuhan, 24.5% of pregnant women reported self-rated anxiety, compared with 10.4% of that in Chongqing, China [6].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of anxiety (assessed by state-trait anxiety inventory) was 38.2% among pregnant women in Italy [8]. The rate of depression (assessed by EPDS) was 35.4% among Turkish pregnant women and 29.6% among Chinese women in the third trimester of pregnancy [5,7]. Although the peak of the epidemic in China has passed, the psychological condition of pregnant women does not seem to improve, as we found that 73 (64.6%), 66 (58.4%) and 62 (54.9%) pregnant women had anxiety, depression and health risk stress,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the severity of the COVID‐19 infection of the mothers was not considered. Clinically, pregnant women with the more severe COVID‐19 infection appear to prefer delivery by caesarean delivery rather than vaginal birth 2–4 . Therefore, it is possible that any beneficial effects of caesarean birth in reducing transmission of COVID‐19 might not be apparent because the severity of COVID‐19 infection was greater in these women.…”
mentioning
confidence: 99%